Creative Product Prototype of Natural Fiber Craft Tray in Rural Vocational Communities - Widodo Widodo; Arif Bintoro Johan; Fajar Dwi Yudanto (VANOS Journal of Mechanical Engineering Education, 2024)
In the digital era, the creative economy is increasingly developing through creative products that have become leading products in every country. one of them is the water hyacinth tray which is one of the superior products of the Kulon Progo community, Special Region of Yogyakarta. The purpose of the study is to apply mechanical engineering science, the frame of this tray will be tested for its feasibility and durability and students can participate in implementing creative product applications that are beneficial to the general public. The research method uses action research with sample data including materials, material density values and material volume lifted by the tray. Testing of the tray frame using Finite Element Analysis (FEA/FEM) to determine the maximum load that can be carried by the tray. The tray frame is loaded to obtain stress propagation, deformation, tensile safety factor and cycle life. The working loads given include 2.9 kg, 3.4 kg and 4 kg while the maximum load in the experiment is 5 kg and 10 kg. The results of the research on the concept of creativity become a basic concept in the development of science and skills. In tray design, steel is the best material for making trays when tested with software.